ANALYSIS OF THE KNOWLEDGE AND ABILITY OF MSME ACTORS IN THE PREPARATION OF FINANCIAL STATEMENTS IN THE PANGALENGAN DISTRICT AREA - Fadjar, Achmad; Mutiara, Senna Nabilla; Marwansyah, Sendi; Elanda, Mochamad Resya; Chresstella, Jesslyn; Sintia (CENTRAL ASIA AND THE CAUCASUS, 2022)
In improving the economy and reducing the number of unemployed, MSMEs have a very large influence. However, there are still many problems that must be faced by MSMEs, one of which is a problem in financial management, especially in the use of knowledge and skills in preparing financial reports. The knowledge and ability of MSME actors is suspected to be a problem in this study. The purpose of this study is to determine the knowledge and ability of MSME actors towards the preparation of financial statements. This research method uses a quantitative approach with research that is survey research, namely by distributing questionnaires to respondents or MSME actors in the Pangalengan District. The objects in this study are MSME actors in the Pangalengan District with the number of respondents as many as 38 SMEs that meet the characteristics of SMEs. In this study, data collection was carried out by distributing questionnaires which were then analyzed using the multiple linear regression method.The results of the study prove that the knowledge and abilities of MSME actors affect the preparation of financial statements.